2018
DOI: 10.1088/1742-6596/988/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Search for the non-canonical Ising spin glass on rewired square lattices

Abstract: Abstract.A spin glass (SG) of non-canonical type is a purely antiferromagnetic (AF) system, exemplified by the AF Ising model on a scale free network (SFN), studied by Bartolozzi et al. [ Phys. Rev. B73, 224419 (2006)]. Frustration in this new type of SG is rendered by topological factor and its randomness is caused by random connectivity. As an SFN corresponds to a large dimensional lattice, finding non-canonical SG in lattice with physical dimension is desireable. However, a regular lattice can not have ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In fact, various spin models on rewired lattices with AF interaction have been probed in connection to SG problem [11,12,13]. Previously it was found that no finite temperature Ising SG phase observed on rewired square lattice for κ = 3 [14]. The study did not pay attention to the role played by the randomness in affecting the existing order phase.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various spin models on rewired lattices with AF interaction have been probed in connection to SG problem [11,12,13]. Previously it was found that no finite temperature Ising SG phase observed on rewired square lattice for κ = 3 [14]. The study did not pay attention to the role played by the randomness in affecting the existing order phase.…”
Section: Introductionmentioning
confidence: 99%